Understanding Consumer Value Dimensions in the Usage of Residential Solar Energy Among Generation Z - Belinda Senooane; Tatenda Chabata (Journal of Consumer Sciences, 2026)
Background: Renewable energy transition has become one of the world’s top priorities in the global effort to curb energy poverty. Yet scant studies on actual residential energy usage among Generation Z (Gen Z) exist. Purpose: This study investigated South African Gen Z consumers’ renewable energy usage through assessing the prevalence of perceived values (hedonic and utilitarian) in household solar energy products. Method: Drawing on the Value-Attitude-Behaviour (VAB) framework, a research model was proposed and tested using survey data from a descriptive research design. A convenience sampling method was used to identify suitable respondents, resulting in a sample of 521 young consumers aged 21 to 28. Quantitative data were collected using an online survey. Partial Least Squares Structural Equation Modelling was applied in testing the hypotheses using SmartPLS version 4. Findings: The results confirmed that all direct relationships in the conceptual model were supported. Both perceived utilitarian value and hedonic value have a significant positive influence on environmental involvement and green attitude. A green attitude also positively affects solar usage. However, environmental involvement was not found to mediate the relationship between perceived value and green attitude. This study is among the first to explore the relationships among perceived utilitarian and perceived hedonic value, green attitude, and environmental involvement in the context of solar energy use, testing for mediation by environmental involvement. Conclusions: For practitioners, this study recommends, among other recommendations, enhancing perceived value in marketing strategies for solar energy products and targeted consumer engagement based on their environmental involvement. Research implication: Marketers, policymakers, and solar energy providers should design value-driven communication strategies that resonate with Gen Z's desire for both functional benefits and emotionally rewarding experiences.